Pemberdayaan Ekonomi Petani Lahan Kering Melalui Pengembangan Agroindustri Tempe Di Desa Segala Anyar Lombok Tengah - Candra Ayu; Wuryantoro; Ibrahim; Nurtaji Wathoni; Andi Iva Mundiyah (Fakultas Pertanian Universitas Mataram, 2020)
All Anyar Village-Pujut District is one of the centers for soybean production in Central Lombok Regency. All Anyar Village in 2018 became the second certified soybean seed breeding ground in NTB after Sukarara Village - Jonggat Subdistrict in 2017. However, the amount of production at the farmer level is only 0.57 tonnes / ha even though the average at the provincial level is 1.3 ton / ha. The low production results in low income from soybean farming. The purpose of this service activity is to motivate and build the participants' self-confidence in the use of free time for productive activities as well as to increase knowledge and skills, participants in service activities in the development of the soybean agro-industry, especially the making of tempe. The results of this service activity show that the participants in the service activities respond positively and participate actively in all programmed activities. The transfer of science and technology can run well where the community service participants have been able to make tempe and its processed products. What is even more important is that the extension participants realize that the use of spare time and work potential in making tempe can be used as a source of food and additional family income.